Retrospective analysis of isolated renal hydatid cysts: A single-center study - Demir, Mehmet; Şengel, Abdulhakim; Yağmur, İsmail and Pelit, Eyyup Sabri and Katı, Bülent and Tunçekin, Adem and Çiftçi, Halil (Journal of Surgery and Medicine, 2021)
Background/Aim: Hydatid disease is a parasitic infection caused by Echinococcus granulosus larvae settling in organs through blood and lymph circulation. Hydatid cysts are often observed in the liver and lungs, and isolated renal involvement is extremely rare. In this study, we aimed to evaluate patients who were diagnosed with an isolated renal hydatid cyst and treated in our clinic. Methods: In this case series, the data of patients with renal hydatid cysts, who presented to our clinic between January 2010 and April 2021, were retrospectively reviewed. Only patients with an isolated renal hydatid cyst were included in the study. Demographic data, clinical findings, laboratory findings, indirect hemagglutination test results, radiological findings, treatment methods, complications and follow-up processes of the patients were evaluated. Results: Eighteen patients (11 males and 7 females) were included in the study. The mean age and cyst diameter of the patients were 29.6 years and 9.2 cm, respectively. Reasons for hospital admission included flank pain (38.9%), palpable mass (22.2%), incidental (16.6%), abdominal pain (11.1%), nausea (5.5%) and hematuria (5.5%). Seropositivity in the indirect hemagglutination test was detected in was detected in 61.1%. Fourteen and four of the patients underwent cystectomy and nephrectomy, respectively. No major postoperative complications were observed in any of the patients. The mean follow-up period was 27 months, during which no local and renal recurrence were observed. Conclusion: Although hydatid cysts are most observed in the liver and lungs, they may also be observed in other organs, especially the kidney. The primary treatment for a renal hydatid cyst should be kidney-sparing surgery. Additionally, albendazole treatment is should be recommended pre- and post-operatively to reduce the risk of inoculation and recurrence.